Conoscere se stessi per avere cura di sé - Luigina Mortari (Firenze University Press, 2009)
The first commitment of education is teaching to care ourselves. There are lots of references to Greek culture but there're also many observations about contemporary authors - Stein, Fu-cault, Hadot. The theory of knowledge is central for this argumentation.